Dialysis-specific factors and incident atrial fibrillation in hemodialysis patients - Seung Don Baek; Soomin Jeung; Jae-Young Kang; Ki Hyun Jeon (Renal Failure, 2020)
Background Atrial fibrillation (AF) is common in end-stage renal disease patients. Besides the traditional risk factors, we aimed to find dialysis-specific factors for developing incident AF. Methods From March 2017 to August 2018, we retrospectively reviewed all outpatient-based prevalent hemodialysis patients in our artificial kidney room, and they were followed up until August 2019. Dialysate calcium concentration (3 versus 2.5 mEq/L), time length (4 versus 3.5 h), frequency (thrice weekly versus twice weekly), dialyzer size (effective surface area of 1.4 m2 versus 1.8 m2), membrane permeability (high flux versus low flux), ultrafiltration rate (mL/kg/hour), and blood flow rate (mL/min) were evaluated. Results Among a total of 84 patients, 15 (17.9%) had newly detected AF with a follow-up period of 21 (13.3–24) months. By performing multivariate Cox regression analysis, blood flow rate (mL/min) and ultrafiltration rate (mL/kg/h) were considered significant factors for developing incident AF (adjusted hazard ratio [HR], 0.977; p = 0.011 and adjusted HR, 1.176; p = 0.013, respectively), while dialysis bath, time length, and frequency, dialyzer size, and membrane type were not considered significant factors. Ultrafiltration cutoff rate of 8.6 mL/kg/h was the best predictive factor for incident AF (area under the curve-receiver operating characteristic [AUC-ROC], 0.746; p < 0.005), while blood flow rate was not considered a significant factor for incident AF in ROC analysis (AUC-ROC, 0.623; p = 0.126). Ultrafiltration rate was largely dependent on interdialytic weight gain (p < 0.005, linear-by-linear association). Conclusion Higher ultrafiltration rate was associated with incident AF in hemodialysis patients.